Studi Pendahuluan Keanekaragaman Genetik Kelapa Sawit Asal Kamerun di PT. Binasawit Makmur - Upit Sarimana; Nurcahyono Indarto; Javier Herrero; Pratiwi Erika; Fahmi Wendra; Zulhermana Zulhermana; Dwi Asmono (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Sarimana U, Indarto N, Herrero J, Erika P, Wendra F, Zulhermana Z, Asmono D. 2019. Genetic diversity preliminary study of cameroon origin oil palm at PT. Binasawit Makmur. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):126-133. A plant breeding program needs genetic diversity information of germplasm, but the source of genetic diversity of oil palm plants in Indonesia is very narrow. In order to increase genetic diversity, the introduction of germplasm from Cameroon was conducted. The purpose of this study was to obtain a useful molecular marker in order to get genetic diversity information in Elaeis guinensis germplasm materials from Cameroon at PT. Binasawit Makmur (BSM). This preliminary research has been done in 2013. In this study, 300 samples of Cameroon oil palm DNA from 99 accessions and 10 samples DNA BSM material were analyzed by 9 microsatellite markers (simple sequence repeat; SSR). The 9 SSR markers used were very informative and we obtained 93 alleles with an average of 10.33 alleles per locus. The value of polymorphism information content (PIC) was around 0.746-0.889. The total genetic diversity was relative high (HT = 0.814). The coordinate analysis showed no groups in both 99 accessions and BSM material. Based on phylogenetic analysis, 9 SSR markers could show the genetic diversity between the populations. To validate this fact, it needs further research using more molecular markers and samples.